PENGARUH AKTIVITAS PARIWISATA TERHADAP PERKEMBANGAN UMKM BERBASIS KEARIFAN LOKAL DI DESA KUTUH KAWASAN EKONIMI KHUSUS NUSA DUA - Yoviniani Yevri Yanseni; I Made Sujana; Putu Ratna Windusara Putri; Fitria Asri Satria Dewi (Yayasan Nusantara Hasana Berdikari, 2023)
The development of the tourism sector in Kutuh Village, South Kuta District, Badung Regency, has had a significant impact on the economic growth of the local community, especially Micro, Small, and Medium Enterprises (MSMEs) based on local wisdom. This study aims to analyze the influence of tourism activities on the development of MSMEs that utilize local culture, traditional crafts, Balinese culinary specialties, and creative economic products of the Kutuh Village community. Sustainable tourism destination management in Kutuh Village can improve the economic welfare of the community through direct involvement in tourism activities. The research method used is a qualitative descriptive approach with observation, interviews, and documentation techniques. The results show that the increase in the number of tourists in the Pandawa Beach area and other tourist destinations encourages increased income, market expansion, and product innovation of MSMEs based on local wisdom